An empirical study on user acceptance of healthcare website. (1st January 2014) - Sun, Jianbin; Lu, Jiaojiao
This paper intends to study the factor influences on behavioural intention and usage behaviour of users of healthcare website according to the user acceptance model of healthcare website, which is based on the unified theory of acceptance and use of technology (UTAUT), perceived risk theory and credibility of online health information. An empirical study is conducted with data collected through questionnaires. SPSS is used for descriptive statistics, reliability and validity analysis of data. Research hypotheses are verified by using AMOS17.0 of structural equation model. Results demonstrate that performance expectancy, social influence and credibility of online health information are the key influencing factors of users' acceptance and usage of healthcare website. In addition, experience can moderate the multiple paths through which the factors influence behavioural intention. Finally, a number of practical and theoretical implications are discussed.